THE INFLUENCE OF POLICY IMPLEMENTATION ON THE EFFECTIVENESS OF ACCELERATION OF ELECTRONIC ID CARD RECORDING - Reyta, Fitriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2018)
The problem in this research is the ineffective yet the acceleration of electronic ID card recording. Based on the phenomenon, the researcher suspects that the problem is influenced by policy implementation variables. Based on these problems, the proposed problem is: